Purified α-Amylase from Bacillus cereus exhibits antibiofilm and antiquorum sensing activities against uropathogenic Escherichia coli, Downregulating fimH, and papC virulence genes: implications for urinary tract infections - Amal M. Abo-Kamar; Abd-El-Rahman A. Mustafa; Lamiaa A. Al-Madboly (BMC Microbiology)
Abstract Background and aim Pathogenic Escherichia coli is a known harmful microorganism that takes advantage of favorable conditions to cause various infections in healthcare settings, such as bloodstream infections related to catheters, as well as infections in the urinary and respiratory tracts. E. coli utilizes biofilm development as a means to enhance its virulence and pathogenicity. This work aims to investigate the antibiofilm activity of α-amylase enzyme against uropathogenic E. coli (UPEC) and its effect on biofilm-regulatory genes. Methodology In this study, we evaluated the antibiofilm activity of α-amylase enzyme by spectrophotometric microtiter plate analysis and confocal laser scanning microscopy. Also, the antibacterial activity of the test enzyme was evaluated by measuring the MIC and MBC levels against UPEC. The quorum-quenching activity of α-amylase enzyme was assessed using a qRT-PCR to evaluate the impact on biofilm-regulatory genes. Results Based on our results, purified α-amylase showed MIC and MBC levels ranged between 128 and 512 µg /ml against UPEC isolates using broth microdilution assay. Crystal violet assay revealed MBIC of 128 µg/ml and MBEC of 256 µg/ml for the purified α-amylase. When the biofilm was analyzed by confocal laser scanning microscope, our results showed inhibition of biofilm thickness (56%) and live/dead cell percentages (43/55%). Furthermore, analysis of the effect on the expression of biofilm-encoding genes showed downregulation of both fimH and papC genes by 57 and 25%, respectively, upon treatment of UPEC with ½ of the MIC (64 µg/ml). Conclusions The results demonstrate that our purified α-amylase from B. cereus exhibits promising antibiofilm activities against UPEC at both phenotypic as well as genotypic levels. These findings suggest that this enzyme may serve as a natural effective tool for removing bacterial biofilms, potentially offering new therapeutic avenues for treating infections caused by UPEC.